Perencanaan Struktur Pemecah Gelombang dengan Sisi Miring pada Kawasan Pesisir ULPLTU Sumbawa - Syahri Wardani; Adi Mawardin (Journal of Applied Civil Engineering and Infrastructure Technology, 2026)
The coastal area of ULPLTU Sumbawa, located in Labuhan Kertasari, Taliwang District, West Sumbawa Regency, is affected by coastal erosion caused by shoreline retreat and wave action. Therefore, the objective of this research is to design a breakwater structure with inclined sides to mitigate the height of incoming waves. In this study, the data used includes primary data through direct field observations, while secondary data consists of wind data, tidal data, topographic data, and bathymetric data. Data processing methods involve wind data analysis, fetch, wave characteristics, bathymetry, and topography. After analyzing all the data, the breakwater structure was planned. The resulting design comprises a mound-type breakwater made of tetrapods and natural stones. It has a slope of 1:1.5 (33.7°), a crest width of 3.7 m, a crest elevation of 3.86 m, a structure height of 5 m, with the main armor layer unit weight W=4,079 kg, the second armor layer weight W/10=544.8 kg, and the core armor layer weight W/200=27 kg. Based on the results of the planning of the breakwater structure, it has been recommended to use local materials to reduce costs and support the local economy by ensuring the quality of materials according to standards. This solution is not only cost-efficient but also environmentally friendly, contributes to environmental conservation, and provides significant economic benefits to the surrounding community.